Experimental Study on Recycled Concrete Aggregates with Rice Husk Ash as Partial Cement Replacement - Naraindas Bheel; Shanker Lal Meghwar; Samiullah Sohu; Ali Raza Khoso; Ashok Kumar; Zubair Hussain Shaikh (Salehan Institute of Higher Education, 2018)
Concrete is highly utilized construction material around the globe and responsible for high depreciation of the raw materials. Consumption of this material in construction industry is arching upward day by day. On the other hand, debris of demolished concrete structures are being dumped as waste. For developing countries such waste is not a good sign and need its proper utilization by recycling it into useful product. In this consequence, this study is an attempt to utilize demolished waste concrete by converting into coarse aggregates. This research was conducted on recycled cement concrete aggregates of demolished structures and Rice Husk Ash (RHA). The purpose of this experimental study is to analyze the mechanical properties of concrete; when cement is partially replaced with RHA and natural aggregates by recycled aggregates (RA). In this study, the cement was replaced by RHA up to 10% by weight of cement. For experimental purpose, total 135 concrete specimens were prepared, cured and tested in Universal Testing Machine (UTM). Finally, laboratory results were compared in terms of compressive and splitting tensile strength made with normal and recycled coarse aggregates. All the specimens were prepared at 1:1.5:3 with 0.50 w/c ratio and tested at 7, 14, 21, 28 and 56 days curing ages. It is observed from experimental analysis that the workability of fresh normal concrete is 7% and 10% greater than recycled aggregates concrete blended with 10% RHA and only recycled aggregates concrete without RHA respectively. The compressive strength increases up to 6%, whilst splitting tensile strength increases 4% at 56 days curing, when the cement is replaced 10% by RHA. It is, further, concluded that with more than 10% RHA replacement with cement, the compressive strength decreases. This study would help the construction experts to use such wasted concrete into useable production of new concrete projects.